Influence of Intraocular Lens Material and Eye Axial Length on Posterior Capsule Opacification Dynamic Rate and Frequency - G. V. Sorokoletov; V. K. Zuev; J. R. Tumanjan; F. M. Gerlyak; V. N. Veshhikova; A. N. Bessarabov; L. V. Agdarova (Oftalʹmologiâ)
Purpose: To evaluate posterior capsule opacification (PCO) formation dynamic rate and frequency in artificial eyes with myopia in different terms after cataract extraction and it’s relation with IOL material. Patients and methods. An evaluation of PCO formationdynamic rate and frequency was done by using a retrospective analysis of YAG-laser assist posterior capsule dissections in different terms after cataract extraction on 45640 eyes of 43520 patients with emmetropia and myopia without concomitant pathology.The mean patient’s age was 73±7 years and the least follow-up after  hacoemulsification was 5 years. All eyes were divided on two groups. The first group included 25339 eyes where a hydrophilic IOL was implanted; the second group included 20301 eyes where a hydrophobic IOL was implanted. Results. At the first group the YAG-laser assist posterior capsule dissection was done on 2128 (8,4%) eyes. It was shown a proportional influence of axial length on PCO frequency but more rapidly the PCO rate increased between 26 to 28 mm and then this parameter had stabilization. The PCO dynamic rate had a normal statistical corresponding in the group with maximum at third postoperative year. At the second group YAG-laser assist posterior capsule dissection was done on 244 (1,2%) eyes. It was shown a proportional influence of axial length on PCO frequency too. But increasing of axial length more than 28 mmincreased PCO rate correspondingly that differ the second group from the first. The PCO dynamic rate had an inversely proportional character in the group. Comparing the PCO frequency in both groups showed that hydrophobic material has less PCO rate with any axial length and every time of follow-up. Conclusion. An IOL’s material plays an important role in PCO formation and PCO formation dynamic rate. Hydrophobic material has a statistically significant less PCO frequency through five-year follow-up in eyes with myopia and emmetropia. The PCO dynamic rate strongly differ between groups with a normal statistical corresponding in group 1 and inversely proportional in group 2.